THE STATE OF SCIENCE IN 2013 - Stallinga, Peter; Khmelinskii, Igor (European Scientific Journal, ESJ, 2014)
The state of science in 2013 is presented. This in comparison to science in earlier times. “Where did we come from, where are we, and where are we going?”